Chapter Managing water commons using mediator variables to bridge the gap between environmental factors and anthropogenic pollution indicators - Vukic Lušic, Darija (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Data analysis of groundwater dynamics requires dynamic panel data modelling. Static models that include δ18O values successfully represent the microbial pollution variations within a closed system characteristic of stock pollution. The need for dynamic modelling using first differences of δ18O values indicates that we deal with flow pollution. Policies regarded as optimal for stock and flow pollutants are different. The question of stock or flow is of great importance to decide whether the regulatory body should use price or quantitative allocation mechanisms.